Meningkatkan Semangat Belajar Siswa Kelas 1 dengan Kegiatan Menempel di SDN Tambakaji 04 Semarang - Aisyah Sisilia Pratyaningrum (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to increase students' interest in studying and understanding the pillars of Islam through the method of attaching pictures. This research was conducted using a qualitative descriptive approach at SDN Tambakaji 04 Semarang. The image affixing method is used to introduce the pillars of Islam interactively by arranging finger images that symbolize each pillar of Islam. The results of the research showed that students were very enthusiastic and showed that students were very enthusiastic and showed increased understanding in arranging the pillars of Islam sequentially. Through observations and interviews, it was found that almost all students could order the pillars of Islam correctly, starting from the shahada to the hajj. This sticking activity not only increases student engagement and retention, but also creates more fun, active and motivating learning. This research proves that the visual approach and method of attaching images is effective in increasing students' interest in learning and understanding.